READINESS OF TEACHERS TO INTRODUCE REMOTE EDUCATIONAL TECHNOLOGIES IN HIGHER EDUCATION - Artykbayeva Е.В; Baktybayev Ж.Ш; Tusubayeva Ж.М; Arystanova А.Ж (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
The article discusses the problem of training university teachers to implement distance-learning technologies in higher professional education. Distance learning technologies have great potential in improving the quality and accessibility of vocational education. The relevance of distance education technologies (DЕT) in Kazakhstan has gained particular importance in connection with the suspension of distance learning from January 1, 2019. The effectiveness of DЕT depends on the degree of implementation of regulatory support, infrastructure, software, digital educational content, but the main factor is the willingness of the faculty to use them. Teachers should know the essence and basic principles of the use of DЕT in higher education, modern platforms for the use of DЕT; вe able to create own online courses and other digital educational resources.